Statistical optimization of bio-mediated silver nanoparticles synthesis for use in catalytic degradation of some azo dyes - Mitali Sarkar (Elsevier, 2021)
The present study deals with optimization of process parameters for the synthesis of silver nanoparticles from outer shell extract of Eucalyptus globulus fruit and maximization of nanoparticles yield. The statistical tool of design of experiments (DOE), following response surface methodology (RSM), was, thus, employed. The synthesized silver nanoparticles were characterized by UV–Vis, FTIR, Raman, DLS, SEM-EDX, FESEM and TEM analyses. The nanoparticle, as catalyst, was utilized for reductive degradation of three azo dyes such as methyl orange, methyl red and congo red in aqueous medium at room temperature. Reductive degradation pathway of the said dyes using NaBH4 and silver nanoparticle catalyst was followed under visible light. More than 90% degradation of the dyes was observed within 10 min for methyl orange, and 20 min for both methyl red and congo red. The mechanism of the degradation process and the kinetic parameters were evaluated. The degradation pathway was found to follow a pseudo first-order kinetic model and the activation energy was evaluated to be 244, 204 and 104 kJ mol−1 for methyl orange, methyl red and congo red respectively. The role of common ions on the degradation efficiency was determined and the process was found effective in the river water system.